The Making of Behavioral Development Economics - Demeritt, Allison; Hoff, Karla (World Bank, Washington, DC, 2018)
A core insight from early behavioral economics is that much of human judgment and behavior is influenced by "fast thinking" that is intuitive, associative, and automatic; very little human thinking resembles the rational thinking that characterizes homo economicus. What is less well-recognized is that innate reliance on cognitive shortcuts means that cultural mental models --categories, concepts, social identities, narratives, and worldviews -- profoundly influence judgment and behavior. Individuals have a cultural "toolkit" or "repertoire" of mental models that they use to perceive and interpret a situation and construct a response. Many researchers have connected cultural mental models to economic development, yet they rarely identify their research findings as "behavioral" economics. This research constitutes a second strand of behavioral economics that illuminates the tight interlinkages between preferences, culture, and institutions and points to new policy opportunities. It brings the discipline almost full circle back to 18th and 19th century perspectives. This essay cautions against strong reductionism in which sociological influences on decision making are squeezed into a rational actor model.